2009
DOI: 10.1017/s1068280500009576
|View full text |Cite
|
Sign up to set email alerts
|

Welfare Impacts of BSE-Driven Trade Bans

Abstract: There is often a need to respond quickly to assess the likely implications of policy changes. Here, an equilibrium displacement model is adapted to study international bans on U.S. beef. An equilibrium displacement model offers a convenient way of quickly predicting the effects of supply and demand shocks. The equilibrium displacement model used here has an international sector, which allows the study of issues that past models with only a domestic sector could not. The estimated welfare loss of U.S. beef prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Considering that the impact of prices and income on consumption can be measured by the elasticities of demand, studies of demand systems for imported products have been carried out in Mozambique and in several parts of the world. For example, for meat: (i) the study about the imported broilers in Mozambique [25]; (ii) the investigation of the competitiveness of meat from different origins in Japan [40]; (iii) the estimation of demand systems for imported meat in Japan [55]. To mention few.…”
Section: Problem Statement and Justificationmentioning
confidence: 99%
“…Considering that the impact of prices and income on consumption can be measured by the elasticities of demand, studies of demand systems for imported products have been carried out in Mozambique and in several parts of the world. For example, for meat: (i) the study about the imported broilers in Mozambique [25]; (ii) the investigation of the competitiveness of meat from different origins in Japan [40]; (iii) the estimation of demand systems for imported meat in Japan [55]. To mention few.…”
Section: Problem Statement and Justificationmentioning
confidence: 99%
“…However, the examples of similar academic research could be found for the other countries. As a rule, such food safety or disease-driven research cases often focus on changes of the structure of the domestic consumption or export/import (Felt, 2011;Mattson, 2005;Mutondo, 2009;Niemi, 2008;Taha, 2013) and welfare changes in a vertical supply chain of the selected agri-food commodities (Brorsen, 2002;Hassouneh, 2009;Niemi, 2006). This paper will contribute to the scarce academic research on the aftermaths of the disease-driven trade bans of Russia and will provide the case of the Lithuanian pork market.…”
Section: The Research On Trade Bans Imposed By Russia In the Agricultmentioning
confidence: 99%
“…Morgan (2001) simulates the impacts assuming different scenarios of the effects of earlier BSE outbreaks in Europe on the international beef market showing that beef exports would return to the baseline level by 2006. Mutondo, Brorsen, and Henneberry (2009) and Panagiotou and Azzam (2010) study the welfare loss of U.S. beef producers due to trade bans after the 2003 BSE outbreaks in the United States and estimate a loss ranging from $500 to more than $700 million annually. Wigle, Weerahewa, Bredahl, and Samarajeewa (2007) study the effects of trade restrictions due to BSE outbreaks in Canada and find that the general equilibrium effect produces gains for consumers that partially offset producers’ losses.…”
Section: Introductionmentioning
confidence: 99%